Un fariseo triste, una peccatrice innamorata e Gesù dal potere divino. La costruzione dei personaggi in Lc 7,36-50 - Kowalski, Marcin (The Biblical Annals, 2015)
The present article focuses on the construction of characters in Luke 7:36-50. The author uses the tools of narrative analysis to illumine the way in which the narrator describes the three main protagonists of the story: Simon, the Pharisee, woman called a sinner, and Jesus. Simon clearly plays a secondary role in the narration serving as a negative background for the presentation of woman and introducing the main theme of the identity of Jesus. The woman, although being presented by the narrator as a sinner, is eventually put forward as a model of love and faith. However, she also plays a secondary role with respect to Jesus around whom all the story revolve. He is the one that attracts all the attention of the story. His voice resounds with authority suppressing even the voice of the narrator and giving interpretation to the behavior of other characters. The image and identity of Jesus, which is the main point of narrator’s interest, goes well beyond the traits of rabbi and master pointing at his divinity.